Alliteration and sound change in early English - Minkova, Donka, 1944- (Cambridge studies in linguistics, 2003)
This study uses evidence from early English verse to reconstruct the course of some central phonological changes in the history of the language. Examination of the behaviour of onset clusters sheds new light on the special treatment of sp-, st-, sk-, and the chronology and motivation of cluster reduction.